AN EXTENSIVE REVIEW ON PRASUGREL - Nagaraju, GV; Subrahmanyam, SN; Pavan Kumar, GV (Journal of Drug Delivery and Therapeutics, 2018)
In an attempt prasugrel increase in the overall use of this medication comparing to the anti thembolytics like heparin and wararin, with less patients complaints includes side effects a significant portion of patients receiving the medication for off label indications. More importantly, this agent is used in a substantial number of patients with known contraindications. Prasugrel are more intense platelet inhibition confirmed by the observation of highest percentage of minor or moderate bleeding among patients taking prasugrel, although there was no significant increase in the rate of severe, major, or life-threatening bleeding.Keywords: prasugrel, thembolytics, wararin, heparin